contestada

Find the value of f(–3) and g(3) if f(x) = –6x + 3 and g(x) = 3x + 21x^–3.
f(–3) = 21 g(3) = 9.78
f(–3) = –18 g(3) = –9.78
f(–3) = –3 g(3) = 30.04
f(–3) = 15 g(3) = 8.22

Respuesta :

Answer:

f(-3)=21

Step-by-step explanation:

Plug in -3 for x. -6•-3=18. 18+3=21.

Answer:

f(–3) = 21 g(3) = 9.78

Step-by-step explanation:

Given functions,

[tex]f(x) = -6x + 3-----(1)[/tex]

[tex]g(x)=3x+21x^{-3}-----(2)[/tex]

Put x = -3 in equation (1),

[tex]f(3) = -6(-3) + 3 = 18 + 3 = 21[/tex]

Put x = 3 in equation (2),

[tex]g(3) = 3(3) + 21 (3)^{-3}=9 + \frac{21}{3^3}=9+\frac{21}{27}=9.777778\approx 9.78[/tex]

Hence, first option is correct.

ACCESS MORE